A Book to Browse and Wonder Through: Visual Representation of Space in Northern Bohemia - Pýcha, Čeněk (Dějiny – teorie – kritika, 2015)
This contribution focuses on the relation between physical space and its visual representation. The author works with the context of landscape photographs and introduces a category of books which are to be browsed and leafed through, meaning that a model reader turns the pages and looks at photographs, thus arriving at a certain notion of space. This book category is applied to representative publications which documented the whole of northern Bohemia in the 1970s and 1980s. Using these sources, the author reconstructs some basic characteristics of creating the image of northern Bohemia at the time and searches for potential sources of conflict, for example in issues surrounding ethnicities and protection of nature. In the second part, the contribution analyses later transformations of visual representation of northern Bohemia in the context of a more general evolution of visual culture. What we tend to start seeing are some new approaches, such as visual comparison between the earlier and current appearance of particular places, and a historicising perspective in general.